Lifetime physical activity and late-life cognitive function: the Rancho Bernardo study. (7th January 2019) - Reas, Emilie T; Laughlin, Gail A; Bergstrom, Jaclyn; Kritz-Silverstein, Donna; Richard, Erin L; Barrett-Connor, Elizabeth; McEvoy, Linda K
Abstract: Background: physical activity in older age has been associated with better cognitive function, but the role of earlier life physical activity is less well understood. Objective: determine associations between physical activity throughout the lifespan and cognitive function in older age. Design: cross-sectional study. Setting: the Rancho Bernardo Study of Healthy Aging in southern California. Subjects: A total of 1, 826 community-dwelling men and women (60–99 years) who attended a research visit in 1988–92. Methods: participants underwent cognitive testing at older age, and reported physical activity as a teenager, at age 30 years, 50 years and currently. For each time-point, participants were classified as regularly active (3+ times/week) or inactive. Results: regular physical activity was associated with better cognitive function, with physical activity at older ages showing the strongest associations. Physical activity in older age was associated with better global cognitive function, executive function and episodic memory, regardless of intensity. Intense physical activity in teenage years was associated with better late-life global cognitive function in women. Teenage physical activity interacted with older age physical activity on executive function; those active at both periods performed better than those active at only one period. Similar patterns of associations were observed after excluding individuals with poor health. Conclusions: regular physical activity in older age, regardless of intensity, is associated with better cognitive function. Physical activity in teenage years may enhance cognitive reserve to protect against age-related decline in executive function. Further research is needed to assess the effect of physical activity across the lifespan on healthy brain ageing.